Damping rate of a massive fermion in a hot medium - Henning, P.A. (Condensed Matter Physics, 2000)
In a hot system every excitation acquires a ﬁnite lifetime, manifesting itself
in a non-zero spectral width. Ordinary damping as well as quantum memory effects arise from this nontrivial spectral function. This report presents
a new method for the self-consistent calculation of the spectral width of
a fermion coupled to massless bosons of scalar, vector and pseudoscalar
type. In accordance with the known procedures of Quantum Electrodynamics, the self-consistent summation of the corresponding Fock diagram eliminates all infrared divergences although the bosons are not screened at
all. The solutions for the fermion damping rate are analytical in the coupling constant g , but not analytical in the temperature parameter, i.e.,
γ ∝ g²T + O(g⁴T log(T /M )) . У гарячому середовищі кожне збудження має скінченний час існування і проявляється ненульовою спектральною шириною. Звичайне
затухання, так само як і квантові ефекти пам’яті, отримується з цієї
нетривіальної спектральної функції. Дана робота представляє новий метод самоузгодженого розрахунку спектральної ширини ферміона, зв’язаного з безмасовим бозоном скалярного, векторного та
псевдоскалярного типів. У відповідності до відомих з квантової електродинаміки процедур самоузгоджене сумування відповідних фоківських діаграм вилучає всі інфрачервоні розбіжності незважаючи на
те, що бозони зовсім не екрануються. Розв’язок для константи ферміонного затухання є аналітичним за константою зв’язку g , але не
є аналітичним за параметром температури, тобто γ ∝ g²T + O(g⁴T log(T /M )) .